Assessing the Role of AI-Based Tax Digitalization and Supervision in Reducing Corruption in Indonesia’s Tax Sector - Puteri Ayu Pratiwi; Rosdiana Mata; Ayu Sartika Pane; Rosmiati Rosmiati; Firyal Nailah Izzatul (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study investigates the implementation of AI-based tax digitalization and enhanced supervision as mechanisms to reduce corruption within the taxation system. Despite ongoing reforms, tax evasion remains a common issue, as illustrated by a 2021 case managed by the Regional Directorate of Taxes in Nusa Tenggara. Artificial Intelligence provides innovative tools for detecting irregularities and preventing fraudulent activities. Adopting a quantitative descriptive design, the research utilizes primary data obtained from 99 tax officers through a census sampling approach, and analyzes the data using descriptive statistics, multiple linear regression, and hypothesis testing. The results indicate that both AI-based tax digitalization and strengthened supervision have a significant and positive impact on tax evasion prevention.